The effect of pH on endo-1,4-Î²-glucanase activity from Bacillus sp. AR 009 (Biodiversitas Journal of Biological Diversity, 2016)
The determinination of the suitable pH condition for maximizing the activity of endo-1,4-Î²-glucanase of Bacillus sp. AR 009 had been done. The acidity range of media for examining the enzyme activities were 4, 5, 6, 7, 8, and 9 at 37Â°C. The experiments show that the value of maximum activity of endo-1,4-Î²-glucanase was 23.068 U/mL at third day incubation with 124.565 mg/L of sugar reduction at pH 7.Key words: pH, Bacillus sp. AR 009, endo-1,4-Î²-glucanase